The association between serum folate and gestational diabetes mellitus: a large retrospective cohort study in Chinese population - Xiao-Hui Liu; Zhi-Juan Cao; Li-Wei Chen; Dong-Lan Zhang; Xiao-Xian Qu; Yu-Hong Li; Yu-Ping Tang; Yi-Rong Bao; Hao Ying (Cambridge University Press, 2023)
Abstract Objective: To investigate the association between folate levels and the risk of gestational diabetes mellitus (GDM) risk during the whole pregnancy. Design: In this retrospective cohort study of pregnant women, serum folate levels were measured before 24 gestational weeks (GW). GDM was diagnosed between 24th and 28th GW based on the criteria of the International Association of Diabetes and Pregnancy Study Groups. General linear models were performed to examine the association of serum folate with plasma glucose (i.e. linear regressions) and risk of GDM (i.e. log-binomial regressions) after controlling for confounders. Restricted cubic spline regression was conducted to test the dosage-response relationship between serum folate and the risk of GDM. Setting: A sigle, urban hospital in Shanghai, China. Participants: A total of 42 478 women who received antenatal care from April 2013 to March 2017 were included. Results: Consistent positive associations were observed between serum folate and plasma glucose levels (fasting, 1-h, 2-h). The adjusted relative risks (RR) and 95 % CI of GDM across serum folate quartiles were 1·00 (reference), 1·15 (95 % CI (1·04, 1·26)), 1·40 (95 % CI (1·27, 1·54)) and 1·54 (95 % CI (1·40, 1·69)), respectively (P-for-trend < 0·001). The positive association between serum folate and GDM remained when stratified by vitamin B12 (adequate v. deficient groups) and the GW of serum folate measurement (≤13 GW v. >13 GWs) Conclusions: The findings of this study may provide important evidence for the public health and clinical guidelines of pregnancy folate supplementation in terms of GDM prevention.